Towards Conceptualising Islamic Community-Based Enterprise: Examination of Some Underlying Principles - Alamsyah, Indra Fajar; Omar, Azura; Sarif, Suhaimi Mhd (Perhimpunan Intelektual Muslim Indonesia, 2022)
This study explores the concept of an Islamic community-based enterprise (CBE) by addressing the fundamental differences between Islamic values and capitalist principles. This approach aims to develop a holistic CBE framework rooted in Islamic teachings, offering an alternative to conventional models dominated by capitalist ideologies. The purpose of this study is to conceptualize an Islamic CBE by reviewing three key components—social entrepreneurship, social capital, and development concepts—from an Islamic perspective. This research employs a conceptual and exploratory approach, analyzing existing literature on community-based enterprises and related topics. It critically evaluates conventional CBE frameworks and their embedded capitalist elements. The analysis reveals that conventional CBE concepts have unresolved limitations due to their capitalist foundations. By integrating Islamic perspectives, this study proposes an alternative model for Islamic CBE that addresses these shortcomings and offers a comprehensive framework for local development. The proposed Islamic CBE framework provides a roadmap for Islamic entrepreneurship that aligns with local conditions and fosters community-based economic development. This approach has practical implications for policymakers and stakeholders seeking to enhance local development through community-based enterprises. Future studies should focus on empirical investigations and the development of measurement tools to validate and refine this conceptual framework. This research serves as a foundational contribution to advancing Islamic community-based enterprise studies.